مجموعة أدوات الإدارة المستدامة للمراعي من أجل نظم رعوية مرنة - Louhaichi, Mounir; Davies, Jon; Gamoun, Mouldi; Hassan, Sawsan; Ouled Belgacem, Azaiez; Abu-Zanat, Mahfouz; Neffati, Mohamed; Tadros, Maher; Rajabov, Toshpulot; Annouri, Laila; Al Rahahleh, Laith; Baqain, Razan; et al. (International Union for Conservation of Nature (IUCN), 2024)
The toolkit (Arabic language) promotes a comprehensive and collaborative strategy, encouraging a multi-stakeholder approach that recognizes the crucial role of rangeland governance in bottom-up landscape restoration. It underscores the importance of incorporating indigenous knowledge and contemporary scientific insights in decision-making to effectively address region-specific challenges. Users can explore a range of Sustainable Rangeland Management (SRM) practices within the toolkit, designed to achieve a balanced level of degradation (LDN) and present significant potential for the rehabilitation and restoration of deteriorated rangeland ecosystems.